Retromolar canal – an essential structure that is often forgotten - Piskórz, Magdalena; Hamruk, Eliza; Portka, Katarzyna; Różyło-Kalinowska, Ingrid (Journal of Stomatology, 2021)
The retromolar canal is the anatomical branch of the mandibular canal. It contains a neurovascular bundle made of thin nerve fibers, veins and arteries surrounded by collagen fibers. The aim of the study was to review information about the retromolar canal presence and its consequences. The canal adjacent to the molar triangle may have different variants that occur at different frequencies. This canal constitutes 46.67% of all mandibular canal branches, making it the most common type of bifurcation, next to the canal branching upstream, buccal-lingual and to the tooth root. Thomas von Arx et al. classified variants of the alignment of the retromolar canal and distinguished five types. The retromolar canal and its content may be of great clinical importance for doctors in the area of the retromolar triangle. The retromolar nerve may contribute to inadequate anesthesia around the retromolar triangle, but this problem can be solved by techniques other than traditional anesthesia. Working in this area, doctors should take into account the possibility of damaging the neurovascular bundle. The analysis of the available literature show that the retromolar canal is not a rare phenomenon in the population. Therefore, should always be taken into account the possibility of its presence and consequences.